Implementasi Qanun No. 11 Tahun 2018 Tentang Lembaga Keuangan Syari’ah Dalam Perspektif Ibnu Khaldun - Redha Maulana (Jurnal Community, 2023)
The implementation of Qanun Shari'a Financial Institutions (LKS) is intended to strengthen the implementation of shari'a economic development in Aceh. The regulation applies to all Acehnese people, both Muslims and non-Muslims, and all agencies or legal entities that conduct financial transactions in Aceh. The pros and cons continue to be highlighted in the implementation of Qanun LKS from various aspects, both services and products that have not been able to replace the role of conventional banks among the people of Aceh. This has an impact on Aceh's economy and the loss of economic justice to the community, both business actors and the lower middle class. Therefore, a research question arises about how is economic justice according to Ibn Khaldun in the implementation of Qanun LKS?. This research is a juridical normative research with an empiric approach and uses secondary data as material for comparing the implementation of Qanun as the primary material. Thus, the results of this study reveal the fact that the implementation of Qanun LKS in Aceh from the perspective of Ibn Khaldun's economic justice is still not well implemented. This sees how difficult the community is in carrying out various economic transactions and some business actors in carrying out economic activities with outsiders in their business.